Analysis of waste handling strategies for riverbanks communities - Syafari, Muhammad Riduansyah; Ridwan, M. Nur Iman; Sugiannor, Sugiannor; Shaddiq, Syahrial (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Waste management is essential to protecting the environment and minimizing its negative impact on human health and the ecosystem. The low participation of riverbank residents in maintaining and creating a clean environment in the river and its surroundings has prompted the Environmental Service to create a program called "River Maharagu" by holding river cleanliness competitions. This research aims to analyze the success of the Environmental Service program by formulating a strategy for handling waste from riverbank communities through a SWOT analysis. This research uses a qualitative approach with a descriptive type. The SWOT analysis results found that (1) Strategy (SO) encourages and facilitates stakeholders to collaborate with the Diaspora and universities to build and develop river ecotourism. (2) Strategy (WO) to build and increase the synergy of stakeholders and youth communities (Karang Taruna) in building and developing river ecotourism and coordinating with the Diaspora. (3) Strategy (ST): River management maintains self-sufficiency in collecting and transporting household waste and continues to motivate residents to dispose of waste properly. (4) (WT) The Environmental Service builds collaboration with universities in providing education to build awareness among riverbank residents.